Understanding the relationship between trainers' qualification, learning success and satisfaction for agricultural capacity development in rural Bihar - Dirk Hauke Landmann; Sabrina Kimmig; Carl Johan Lagerkvist (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2018)
Within capacity development, the type and quality of the trainer can play a crucial role in promoting farmers' capacity. Hence, the main purpose of this paper is to examine the relationship between trainers' qualification and learning success and satisfaction of small-scale farmers during training activities in Bihar, India. Moderated mediation analysis is utilized to measure the direct and indirect effects of trainers' qualification on learning success and satisfaction. Therefore, the psychological constructs of attitude and perceived control from the Theory of Planned Behaviour (TPB) operate as mediators, subjective norms act as moderator, and gender and age serve as covariates. The results do not indicate a distinction of satisfaction among farmers regarding trainer qualification. However, learning success decreases with an academically educated trainer. The change of attitude during the training has a significantly positive influence on satisfaction. Subjective norms also influence the participants' satisfaction positively. Thus, we suggest for practical implications combining an expert trained on-the-job as the main trainer with an academically educated trainer integrated via modern technologies. In addition, the social environment has to be addressed within the training. Besides the professional background, it is important that trainer gets trained on teaching methods and other soft skills. The results further show that the behavioural constructs are relevant in the field of agricultural education and extension. Theoretical implications can be drawn regarding the improvement of this conceptual framework and other related studies. Whilst various studies have addressed the identification of farmers' capacity development preferences, few have investigated the relationship between trainer qualification, learning success and satisfaction.
Keywords: 330; agricultural training; trainer qualification; moderated mediation; small-scale farmers; India